2012
DOI: 10.3945/jn.112.164947
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Enhances Intestinal Integrity and Inhibits TLR4 and NOD2 Signaling Pathways in Weaned Pigs after LPS Challenge3

Abstract: Long-chain (n-3) PUFA exert beneficial effects on inflammatory bowel diseases in animal models and clinical trials. In addition, pattern recognition receptors such as toll-like receptors (TLR) and nucleotide-binding oligomerization domain proteins (NOD) play a critical role in intestinal inflammation. We hypothesized that fish oil could alleviate Escherichia coli LPS-induced intestinal injury via modulation of TLR4 and NOD signaling pathways. Twenty-four weaned piglets were used in a 2 × 2 factorial design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
277
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(296 citation statements)
references
References 45 publications
(69 reference statements)
16
277
1
2
Order By: Relevance
“…After receiving the control, 1.0% glycine and 2.0% glycine-supplemented diets for 28 days, the pigs were given an intraperitoneal injection of LPS at 100 g/kg BW or the same volume of 0.9% NaCl solution. The LPS dose was used according to our previous studies (25,28,29), which demonstrated that this dose of LPS caused acute tissue injury in weaned pigs. After administration with LPS or 0.9% NaCl solution, all piglets were deprived of feed until slaughter to avoid the potential effects of LPS-caused feed intake reduction on variables in blood and muscle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After receiving the control, 1.0% glycine and 2.0% glycine-supplemented diets for 28 days, the pigs were given an intraperitoneal injection of LPS at 100 g/kg BW or the same volume of 0.9% NaCl solution. The LPS dose was used according to our previous studies (25,28,29), which demonstrated that this dose of LPS caused acute tissue injury in weaned pigs. After administration with LPS or 0.9% NaCl solution, all piglets were deprived of feed until slaughter to avoid the potential effects of LPS-caused feed intake reduction on variables in blood and muscle.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA extraction, quantification, reverse transcription, and real-time quantitative PCR were conducted according to the method as previously described (28). Briefly, total RNA was extracted from muscle samples with the TRIzol reagent (No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both in vivo and in vitro studies have reported antiinflammatory activities of DHA in the brain especially in microglia (Laye, 2010;Orr and Bazinet, 2008). At the cellular level, brain DHA modulates several proinflammatory signalling pathways in microglia such as TLR signalling and nucleotide-binding oligomerization domain protein (NOD) signalling (De Smedt-Peyrusse et al, 2008;Liu et al, 2012), inhibits JUNK , and reduces or blocks NF-kB signalling (De Smedt-Peyrusse et al, 2008;Orr et al, 2013). The inhibitory effect of DHA on proinflammatory signalling pathway could be mediated by both non-genomic and genomic effect.…”
Section: How Do N-3 Pufa Mechanisms Control Neuroinflammation?mentioning
confidence: 99%
“…Ocorre aumento da altura das vilosidades e melhora a função da barreira intestinal indicada pela diminuição da atividade da diamina oxidase no plasma e aumento da expressão de proteínas tight-junction como ocludina e claudina-1 no epitélio intestinal (LIU et al, 2012 Além disso, permitirá o desenvolvimento de novas terapias anti-obesogênicas que têm como alvo vias intracelulares envolvidas no processo inflamatório dos tecidos responsivos à insulina, como fígado e tecido adiposo, e ateroscleróticos, como a aorta torácica e a gordura perivascular.…”
Section: áCidos Graxos E a Ativação Dos Receptores Tlrsunclassified